Oxidative stress and imbalance of serum trace mineral metabolism contribute to bovine respiratory disease in dairy calves - JOSHI, VIVEK; BHANUPRAKASH, A G; MANDAL, R S K; ALAM, S; GUPTA, V K; DIMRI, UMESH (The Indian Journal of Animal Sciences, 2018)
Bovine respiratory disease (BRD) is the most common infectious cause of clinical disease and death in young calves. The study was undertaken to scrutinize a relationship between tissue damage by oxidative stress, concentrations of serum trace minerals and clinical status of calves during BRD. The method of clinical scoring and thoracic auscultation were used to screen and select infected calves. In this study, comparison of lipid peroxides (LPO), antioxidant enzymes and serum trace minerals was done between BRD infected and healthy subjects (18 calves in each group). The infected group was further divided into 3 subgroups according to clinical scores (CS) (5,6,7). The blood LPO levels were significantly higher in BRD infected calves. The antioxidative activities of superoxide dismutase, reduced glutathione, catalase and serum uric acid were significantly lower in BRD infected calves. The concentrations of trace minerals (copper, zinc, selenium) were significantly reduced during BRD. All hematobiochemical parameters varied proportionately with the CS of infected calves. These findings demonstrated simultaneous occurrence of increased oxidative stress and depletion of antioxidative trace minerals during BRD in calves. A strong correlation exists between severity of oxidative stress and CS of calves.